EXPLORING TEACHER’S PERSPECTIVE ON EFL STUDENTS’ DISRUPTIVE BEHAVIOR IN EFL CLASSROOM - Amsar Ramadhan; Ahmad Talib; Hasriani G (Universitas Negeri Makassar, 2026)
This research aims to explore teachers’ perspectives on managing disruptive student behavior in EFL classrooms. It employs a qualitative approach using a case study design. Data were collected through interviews and observations. The subject of this study is an English teacher at SMAN 9 Kepulauan Selayar who deals with disruptive student behavior in EFL classrooms. The results of the research show that teachers have diverse perspectives on five types of disruptive behavior: classroom disruption, aggression, confrontation, disengagement, and wandering. Most of these behaviors, such as classroom disruption, verbal aggression, disengagement, and wandering, are perceived negatively because they disrupt students’ concentration, hinder the learning process, and create an unproductive classroom atmosphere. Meanwhile, teachers exhibit a more neutral perspective toward physical aggression, passive aggression, and confrontation due to the limited occurrence of these behaviors or differing interpretations of them.